High-altitude temporary systems and macroinvertebrate composition in La Nina cycle, Maloti-Drakensberg - Moyo, Sibusisiwe (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
The Maloti-Drakensberg Mountain is an important water catchment area for South Africa and Lesotho. It is rich in biodiversity in terms of endemic flora and fauna and has a high density of temporary wetlands in the form of Afromontane tarns and rock pools. There is, however, limited information on the distribution of macroinvertebrates in these ecosystems and environmental factors that drives their composition. To that end, this study investigated macroinvertebrate diversity and the effect of environmental factors on community assemblage in the Maloti-Drakensberg Mountain temporary wetlands, specifically tarns and rock pools. The main aims were to describe the abundance, diversity, and distribution of macroinvertebrates in temporary wetlands in the Maloti-Drakensberg Mountain. Furthermore, it aimed to investigate the effect of environmental variables on habitat structuring, spatial variations, and macroinvertebrate community composition in tarns and rockpools in the Maloti-Drakensberg Mountain. Seventy temporary wetlands (29 tarns and 41 rock pools) were surveyed over a once-off sampling (3 March "“ 7 April 2022). The wetlands were from 3 provinces including Eastern Cape, Free State, and KwaZulu-Natal. 15278 individual macroinvertebrates from 13 orders, 35 families, and 46 genera were collected and identified. Species accumulation curves incorporating both tarns and rock pools showed that observed results were significantly lower than Chao 1 and Chao 2 estimates meaning that the sampled sites were not enough to provide a comprehensive picture of the biodiversity in the region. This was also observed for rock pools when the temporary wetlands were analysed separately, however, the Chao 1 and Chao 2 values for tarns were almost equal to the observed values implying that sampled sites were enough to give a detailed picture of macroinvertebrate composition in tarns. Tarns and rock pools were significantly different in terms of species richness and Shannon-Wiener diversity index but showed no significant differences for relative abundance and Pielou's evenness. Of the 35 families identified, 19 were considered core taxa with Dytiscidae and Corixidae being the most dominant. Additionally, there was moderate Nestedness metric based on Overlap and Decreasing Fill (NODF) value of 33.05369, with 32 out of 35 families being idiosyncratic. Predators were the dominant feeding group with omnivores being the least common. Non-Metric multi-Dimensional Scaling (NMDS) and PERMANOVA results showed that tarns and rock pools supported distinctly different macroinvertebrate communities per wetland type and location respectively. Physicochemically, tarns and rock pools were significantly different in terms of water temperature, depth, area, and chlorophyll-a concentration with tarns exhibiting higher values. Temporary wetlands in the sampled localities differed in terms of pH, EC, DO, water temperature, altitude, and phosphate. Principal Component Analysis showed that tarns were positively associated with area and depth whereas rock pools with phosphate. Akaike's Information Criterion (AICc) selection showed that area, pH, and water temperature were significantly influencing community assemblage in temporary wetlands. Furthermore, area significantly influenced all four measured biodiversity indices: relative abundance, species richness, Pielou's evenness and Shannon-Wiener Index, with water temperature also influencing relative abundance and altitude, species richness. Overall, the species composition showed that the sites were sampled later in the hydroperiod as evidenced by the dominance of active dispersers. The extended distribution of Prosthetops gladiator in the Eastern Cape highlights the need for extensive surveys to provide valuable insight into the distribution patterns of macroinvertebrates in the region. Furthermore, the interplay between physicochemical variables and biodiversity indices emphasized area, water temperature and pH as significant factors. However, their limited explanatory power suggests that obscure factors also influence the diversity cementing the need for further exploration of these enigmatic systems. Taxonomic challenges, especially regarding large branchiopods, hindered precise species distribution and conservation status determination. This study is the first to provide a comprehensive list of macroinvertebrates from temporary wetlands in the Maloti-Drakensberg Mountain. These results establish a valuable baseline for future biological monitoring studies, particularly in assessing species composition and responses to anthropogenic activities. It is a timeous study considering the sensitivity of these systems to climate change as they act as sentinel sites hence the need for foundational data on which to make future projections.
Keywords: Maloti-Drakensberg Transfrontier Conservation and Development Area (Lesotho and -- South Africa); Mountain animals; Tarn; Mountain watersheds; Biodiversity; Macroinvertebrate; Ecological community assembly